Chemical Analysis of Soil Samples from Bodla Block, Kabirdham District, Chhattisgarh, and Treatment Strategies for Improving Soil Quality - Kumar, Ashwani; Shrivastava, Shilpi (Journal of Neonatal Surgery, 2025)
Soil quality degradation has emerged as a major constraint to sustainable agricultural productivity in central India, particularly in rain-fed and intensively cultivated regions. The present chemistry-based research investigates the physicochemical characteristics of soil samples collected from the Bodla Block of Kabirdham District, Chhattisgarh, with the objective of identifying key nutrient imbalances, salinity–alkalinity issues, and organic matter deficiencies. Standard analytical procedures were employed to evaluate soil pH, electrical conductivity, organic carbon, macronutrients (N, P, K), secondary nutrients (Ca, Mg, S), and micronutrients (Fe, Zn, Cu, Mn). The results indicate moderately alkaline soil conditions, low organic carbon content, nitrogen deficiency, and marginal micronutrient availability, which collectively limit crop productivity. Based on the chemical diagnosis, targeted soil treatment strategies including organic amendments, micronutrient supplementation, pH correction, and integrated nutrient management are proposed. The study provides quantitative evidence-based recommendations for improving soil fertility and long-term soil health in Kabirdham District